Assessing juicy elements in interactive infographics - Campos, Bruno (My University, 2025)
Juiciness refers to the use of various audiovisual effects that are triggered in response to user interactions. This study explores the presence of juicy elements in interactive infographics, thereby extending the investigation of juiciness beyond traditional gaming contexts. Methodology: A descriptive research approach, employing content analysis, was used to evaluate a sample of interactive infographics published between 2010 and 2024. The sample was collected from four prominent sources, and each visualization was analyzed using a binary classification system (YES or NO) to indicate the presence of the identified juiciness elements: animation, particles, audio feedback, screen shake, and persistence. Results: Overall, the findings indicate that juicy elements are present in certain interactive visualizations, though not universally across all examples. The data revealed that animation appeared most frequently, with an occurrence rate of 73.85%, followed by particles (20.51%), audio feedback (5.64%), persistence (4.1%), and screen shake (1.03%). Furthermore, 25.64% of the visualizations contained no juicy elements. Discussion: The findings from the analysis reveal that juicy elements are present in a significant number of interactive visualizations, but none of the visualizations analyzed incorporated all five juicy elements simultaneously. Despite the presence of some juicy elements, no single visualization captured the full essence of juicy design, which ideally offers a high level of feedback from minimal user input. Conclusions: While no single visualization incorporated all five juicy elements, combinations of up to four were observed, suggesting that juiciness does not require a uniform or exhaustive application of all elements.
Keywords: infographics; data visualization; interactive; engaging design